Novel CLCNKB Mutations Causing Bartter Syndrome Affect Channel Surface Expression. Issue 9 (12th June 2013) - Keck, Mathilde; Andrini, Olga; Lahuna, Olivier; Burgos, Johanna; Cid, L. Pablo; Sepúlveda, Francisco V.; L'Hoste, Sébastien; Blanchard, Anne; Vargas‐Poussou, Rosa; Lourdel, Stéphane; Teulon, Jacques
<x xml:space="preserve">Abstract</x> Bartter syndrome type 3, a hereditary disease characterized by renal salt wasting, is associated with mutations in the CLCNKB gene encoding the chloride channel ClC‐Kb, which mediates the basolateral step of chloride absorption in the distal nephron. Investigating the functional consequences of seven mutations in Xenopus laevis oocytes, we identified two classes of mutants: mutants displaying no electrical activity and low total protein expression, and partially conducting mutants with unaltered protein abundance. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>